Peningkatan Perolehan Uranium, Torium, dan Logam Tanah Jarang dalam Residu Pelarutan Parsial pada Pengolahan Monasit - Fatihah, Novita Sari; Anggraini, Mutia; Pratama, Afiq Azfar; Widana, Kurnia Setiawan (EKSPLORIUM, 2021)
Monazite is a by-product of tin processing containing phosphate, rare earth elements, and radioactive elements such as uranium and thorium. These elements can be utilized optimally if separated from one another through processing. Monazite processing includes decomposition, partial dissolution, and precipitation processes. The separation of rare earth elements from radioactive elements in monazite is carried out through a partial dissolution process, but the separation is not optimal so that further processes are needed to increase the recovery of these elements. In this study, the process was carried out using two methods, namely total dissolution with hydrochloric acid (HCl) which aims to dissolve all elements in the precipitate and precipitation with ammonium hydroxide (NH4OH) which aims to separate radioactive elements and rare earth elements. Both methods were carried out under optimum process conditions with various variations in pH, temperature, and time. Based on observations, it was found that the optimum solubility of each element was 67.6% uranium, 15.3% thorium and 50.8% LTJ under the dissolving process conditions of pH 1, at 80°C for 2 hours. While in the deposition process, the precipitation recovery of each element is 57% uranium, 75.7% thorium, 4.8% rare earth metals at pH 6 conditions. Based on these data, it can be concluded that uranium, thorium, and rare earth elements can be dissolved at pH 1, at 80°C for 2 hours, and can be separated at pH 6 precipitation conditions.